Independent Curriculum From The Perspective Of Ki Hadjar Dewantara's Philosophical Thought - Alfret Benu; Marzuki Marzuki (PT Publikasiku Academic Solution, 2024)
Merdeka Curriculum, an educational initiative introduced by Nadiem Makarim, Indonesia's Minister of Education and Culture, has several differences with Ki Hadjar Dewantara's educational concept. In its implementation, the Merdeka Curriculum emphasizes student freedom in determining the course of learning, promotes creativity, and encourages project-based learning. However, this may conflict with Ki Hadjar Dewantara's concept, which prioritizes the role of the teacher as a facilitator in directing student development. This research aims to understand the factors that cause this phenomenon by using Ki Hadjar Dewantara's perspective as an analytical tool. This research uses a descriptive qualitative approach with a literature study method through several stages including library data collection, recording, reviewing data sources, and processing information. The results show that Ki Hadjar Dewantara's concept of education also emphasizes student-centered learning by respecting their individuality and a holistic approach to education. Unfortunately, in the implementation of the Merdeka Curriculum, the focus on respecting students' individuality and developing moral, emotional, and physical aspects may not be a priority. In addition, other important aspects such as education for students' daily lives may also not get enough attention in the Merdeka Curriculum. The link between learning in the curriculum and students' real lives may become less clear.